(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To detect the malignant cancer oust issues in the breast, various techniques are used. These are Mammography ,MRI, and Ultrasound etc. These technologies are miserable during examining. The Microwave Breast Imaging technique generates scattered signals and it detects abnormal tissues after transmission and reception of Microwave signals.Therefore,1X4 array antenna is designed. It detect the tumor at early stage. This array antenna is more specific to detect the malignant issues. The array antenna has 1X4 arrays, with Defected Ground Structure (DGS).It will increase efficiency of this model. This model is used in ISM (Industrial, Scientific, and Medical).It is designed for center frequency2.4GHz. The input return loss should be greater than 10. FR4 is used as Substrate. Theoretical modeling and simulation by HFSS Software is done to optimize antenna parameters. Three antennas namely Microstrip patch antenna, 1 x 4 MSP array antenna and 1 x 4 MSP array antenna with DGS are fabricated and the experimental results are verified in an anechoic chamber of millimeter wave and antenna lab. It is found that the experimental results match the simulated results. It is found that array and DGS enhances the antenna parameters like antenna gain, return loss, VSWR and bandwidth at 2.4GHz frequency for ISM band applications.